Audit Committee Characteristics and Accounting Conservatism. (7th January 2015) - Sultana, Nigar
<x xml:space="preserve">Abstract</x> This study examines the association between four pivotal audit committee characteristics and accounting conservatism. Using a sample of 7, 668 Australian firm‐year observations from 2004 to 2012, a positive association is found between accounting conservatism and: (a) a director with financial expertise on the audit committee; (b) an experienced director on the audit committee; and (c) frequency of audit committee meetings. Within an agency theoretical framework, results suggest that audit committees act as effective monitoring mechanisms in restricting management's opportunistic behaviour and overstatement of earnings. Results also suggest that regulators (and other stakeholders) should pay greater attention to the financial expertise, experience of members and meeting frequency of the audit committee when judging the committee's value.